2006
DOI: 10.1108/14635770610644628
|View full text |Cite
|
Sign up to set email alerts
|

Performance measures in English small and medium enterprises: survey results

Abstract: PurposeTo determine the current state of knowledge related to performance measures and their degree of implementation in small and medium enterprises (SMEs) in England.Design/methodology/approachThe paper starts with a literature review and then goes on to discuss the methodology used. The survey is briefly presented together with the analysis of the resultant data. General opinions regarding performance measurement in English SMEs are described, including the most important measures and the biggest obstacles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 26 publications
3
62
0
13
Order By: Relevance
“…They also found that smaller businesses were most likely to be dissatisfied with their management accounting systems. In a later study, Sousa et al (2006) determined the current state of knowledge related to performance measures and their degree of implementation in SMEs in the U.K. Overall, financial measures were the most widely used, while innovation and learning measures were rated less important and were less used.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that smaller businesses were most likely to be dissatisfied with their management accounting systems. In a later study, Sousa et al (2006) determined the current state of knowledge related to performance measures and their degree of implementation in SMEs in the U.K. Overall, financial measures were the most widely used, while innovation and learning measures were rated less important and were less used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researches into management accounting among SMEs such as by Hopper et al (1999); Jarvis, Kitching, Curran, & Lightfoot (2000); Marriott & Marriott (2000); Reid & Smith (2002) and Sousa, Aspinwall, & Rodrigues (2006) are still fragmented and focused on a different aspects of management accounting. Therefore there is only a few pieces of information regarding the use of MAPs in SMEs have been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The topic of management accounting information employed in the enterprise was more interested in scholars, however, there is a dearth of studies regarding the use of management accounting among SMEs. Studies of management accounting among SMEs conducted by by Hopper et al (1999), Jarvis et al (2000), Marriott et al (2000); Reid & Smith (2002), and Sousa et al (2006) are still fragmented and focused on a different aspects of management accounting. Mitchell & Reid (2000) argued that the expertise and capacity to innovate in management accounting is less likely to exist.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also found that smaller firms were most likely to be dissatisfied with their management accounting systems. Sousa et al (2006) determined the financial measures were the most widely used, while management accounting system was regarded less important and was less used.…”
Section: First Promotion Of the Role Of Management Accounting In Smementioning
confidence: 99%
“…Non-financial performance was used by Tuanmat & Smith (2011) to measure organizational outcome, as with respect to product availability, product quality, and sales service and support. Sousa, et al (2006) also used productivity, customer satisfaction, and customer needs to assess the company's performance. Furthermore, Isobe, et al (2008) developed a list of long-term performance indicators, including new product and technological innovations.…”
Section: The Business Performance Conceptsmentioning
confidence: 99%